Incidencia del liderazgo educativo y el trabajo en equipos, en el clima organizacional del colegio técnico agropecuario Manú, de la parroquia Manú, del cantón Saraguro, de la provincia de Loja, en el período 2012-2013. Lineamientos alternativos - Bustan Villa, Judith Elvira (2014)
This research project concerning: The Impact of Leadership and Work Teams Organizational Climate on Agricultural Technical School " Manu " , of the Parish Manu Saraguro Canton of the Province of Loja , in the period 2012 -2013 , aims , determine the incidence of Educational Leadership and Organizational Work Climate Agricultural Technical College " Manu " To carry out the project , the methods have been applied : scientific , analytical, statistical , comparative and inductive and inductive method , which enabled them know the problem , check the hypotheses and obtain all the information , techniques used were the interviews conducted with the authorities, and surveys for teachers , students and parents, which have been shown statistically to its subsequent interpretation This paper contains topics, Educational Leadership, Team Work and Organizational Climate are the same as the theoretical elements in which the project is based. There is also the approach of the hypothesis and its operation reflected in the variables, indicators and indices. The results that have been obtained to the conclusion that there are certain shortcomings in Leadership in authority and teamwork within the Agricultural Technical School " Manu " , a small degree hindering organizational climate in which members play the educational community. In this situation, the guidelines have been established alternative, which serve as the basis for the training that aims to update and innovate the staff of the institution, improve educational leadership exercises authority and provide appropriate mechanisms to ensure teamwork, generating an organizational climate suitable for the professional performance of all educational personnel.